Resolution towards fulfilling UMP’s vision as a leading technology university - Rohana, Othman (2018)
For the very first time, all 80 members of the University Board of Directors (UBD) and the university management including the deans, directors, heads of department and senior officers got together in a programme called UMP Team Excellence.